Գործարքային ծախսերի էությունը և տնտեսագիտական մեկնաբանությունը - Ռադիկ Վերդյան (ՀՀ ԳԱԱ հրատ.)
На нынешнем этапе экономического развития Республики Армения актуальными стали вопросы определения, измерения, экономического значения и экономической интерпретации транзакционных издержек. Это обусловлено спецификой установления рыночных отношений и присущей экономике слабой развитостью институциональной среды. Тем не менее основной сложностью теории транзакционных издержек является ясность в разграничении, оценке и измерении транзакционных издержек на методологическом и статистическом уровне.At the current stage of the RA economic development the definition, calculation, economic significance and economic interpretation of transaction costs have become relevant issues. This is explained by the specifics of formulation of market relationships and the underdevelopment of the institutional environment inherent to the economics. Nevertheless, the key challenges of the transaction costs theory are the clarity in distinguishing, estimation and measurement of transaction costs at methodological and statistical levels.
Keywords: Social Sciences; Economic Theory